Gender norms and health: insights from global survey data - Weber, Ann M; Cislaghi, Beniamino; Meausoone, Valerie; Abdalla, Safa; Mejía-Guevara, Iván; Loftus, Pooja; Hallgren, Emma; Seff, Ilana; Stark, Lindsay; Victora, Cesar G; Buffarini, Romina; Barros, Aluísio J D; et al. (The Lancet (British edition), 2019)
Despite global commitments to achieving gender equality and improving health and wellbeing for all, quantitative data and methods to precisely estimate the effect of gender norms on health inequities are underdeveloped. Nonetheless, existing global, national, and subnational data provide some key opportunities for testing associations between gender norms and health. Using innovative approaches to analysing proxies for gender norms, we generated evidence that gender norms impact the health of women and men across life stages, health sectors, and world regions. Six case studies showed that: (1) gender norms are complex and can intersect with other social factors to impact health over the life course; (2) early gender-normative influences by parents and peers can have multiple and differing health consequences for girls and boys; (3) non-conformity with, and transgression of, gender norms can be harmful to health, particularly when they trigger negative sanctions; and (4) the impact of gender norms on health can be context-specific, demanding care when designing effective gender-transformative health policies and programmes. Limitations of survey-based data are described that resulted in missed opportunities for investigating certain populations and domains. Recommendations for optimising and advancing research on the health impacts of gender norms are made.